2019
DOI: 10.1155/2019/2946158
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Application of BP Neural Network Model in Risk Evaluation of Railway Construction

Abstract: Chinese railway construction project is an important part of the implementation of the “Belt and Road” strategy, and the risk evaluation of overseas railway construction is the primary link of the project. Firstly, this paper mainly analyzes the Asian and European countries along the railway construction project, establishes a railway construction project risk evaluation system, and synthesizes various risk factors. Secondly, it establishes two independent BP neural network models by using different training a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…In connection with the above shortcomings, experts are actively looking for a technique that would give a high-quality outcome that can adapt to the constant changes of the threat landscape, exclude the inadequate and irrelevant expert assessments, and allow reuse of previous evaluations. The most promising method in this area is the artificial neural network (ANN) approach, which addresses the challenges of existing methods, particularly with regards to flexibility and adaptability, although it requires a lot of time and intellectual resources [39][40][41][42]. In addition, the ANN has intelligent features such as self-learn, and thus it is possible to find the best way to solve the problem, accumulating information about external and internal processes.…”
Section: Shortcomings Of Existing Methods and Possible Solutionsmentioning
confidence: 99%
“…In connection with the above shortcomings, experts are actively looking for a technique that would give a high-quality outcome that can adapt to the constant changes of the threat landscape, exclude the inadequate and irrelevant expert assessments, and allow reuse of previous evaluations. The most promising method in this area is the artificial neural network (ANN) approach, which addresses the challenges of existing methods, particularly with regards to flexibility and adaptability, although it requires a lot of time and intellectual resources [39][40][41][42]. In addition, the ANN has intelligent features such as self-learn, and thus it is possible to find the best way to solve the problem, accumulating information about external and internal processes.…”
Section: Shortcomings Of Existing Methods and Possible Solutionsmentioning
confidence: 99%
“…Dong et al studied the international transport network and indicated that the massive costs, the environment, and technology were the main restraining factors for constructing transport corridors [25]. Yang et al and Jin et al concluded that economic risk (risk brought about the social economic situation of the target region), population risk (average quality of people's life of the target region), traffic risk (the current national overall traffic level of the target region), and political risk (the current domestic policies and regulations of the target region) were the main risks that need to be considered for railway construction [26,27]. Liu et al established an evaluation index system for investment risk of highway construction, in which political risk, economic risk, environment risk, management risk, and technological risk were listed as five risks [28].…”
Section: Risk-related Factors In Constructing Transport Corridorsmentioning
confidence: 99%
“…(3) Policy-related risk. Policy incentives are important for the construction of transport infrastructure [26][27][28]. Preferential policies often come along with supporting measures such as tax deductions and exemptions, which can bring in capital, projects, and other factors, and they can significantly promote regional economic development and the construction of transport infrastructure.…”
Section: Risk-related Factors In Constructing Transport Corridorsmentioning
confidence: 99%
“…Among these models, the BP neural network is currently the most popular neural network model in application. It has the universal advantages of all neural networks, self-learning and self-adaptive ability, nonlinear mapping ability, and high fault-tolerance rate (Yang et al, 2019). The BP algorithm's main idea is to divide the learning process into two stages; the first stage is the forward propagation process.…”
Section: Introductionmentioning
confidence: 99%